Jaboticaba (Myrciaria cauliflora (Mart.) O.Berg. [Myrtaceae]) - Almeida Teixeira, G. H. de; Berlingieri Durigan, M. F.; Durigan, J. F. [UNESP]; Yahia, E. M. (Woodhead Publ Ltd, 2011)
Jaboticaba is a small tree, native to the central-south of Brazil. Among the well-known species the most important are the Myrciaria cauliflora (DC) Berg and the Myrciaria jaboticaba (Vell) Berg which produce adequate fruit for both industry (jams, preserves, liqueur and wine) and fresh consumption. This chapter presents the origin, botany, morphology, structure, nutritional value and health benefits of this fruit. It then reviews its postharvest physiology, maturity and quality components, as well as preharvest and postharvest factors which affect fruit quality, problems with physiological and pathological disorders and pests. It also discusses postharvest handling practices and processing.
Keywords: Myrciaria jaboticaba; phytochemistry; antioxidant; postharvest; processing